Social Media’s Negative Impact on Mental Health Subjugated by the Advantage on Young Adults - Madeline Lydia Hiustra; Aurelia Venus Angelica; Christian Haposan Pangaribuan (Business Economic, Communication, and Social Sciences Journal (BECOSS), 2023)
The present research aims to investigate whether presumed negative effects of social media use on mental health have been outweighed by positive factors that contribute influential advantages. Previous research has demonstrated that social media has only negative effects on a person by emphasizing that social media is a major contributor to poor mental health and thus this research examines the relationships between social media impact on learning new knowledge and increased productivity, learning new knowledge and increased productivity on task performance, and direct social media impact on task performance. Researchers used a quantitative approach, collecting questionnaire from 100 respondents that was distributed to young adults (18-26 age), who are currently located in Jakarta, Indonesia. Contrary to what has often been assumed, social media is linked with task performance outcomes. Correlation and data analysis concluded that social media were significantly related with positive associations. Adoption of social media that is used correctly is the main driving force of the beneficial outcomes, which will be explained by the hypotheses centered on direct relationship of social media impact and task performance. The future implications of this study will be discussed.